Demonstration of serum monoclonal immunoglobulin in a case of non-secretory myeloma by immunoisoelectric focusing. Issue 7 (July 1985) - Sheehan, T; Sinclair, D; Tansey, P; O'Donnell, J R
Abstract : A paraprotein band in non-secretory myeloma was shown using a highly sensitive technique of immunoisoelectric focusing. The published work concerning non-secretory myeloma is briefly reviewed.